The Relationship of Personal Hygiene and the Use of Personal Protective Equipments with Dermatitical Complaints in Fisherman of Sugih Waras Village Pemalang District - Aswin Dwi Prasetyo; Siti Musyarofah; Ratna Muliawati; Baju Widjasena (Proceedings of the International Conference on Nursing and Health Sciences, 2021)
One of the most common occupational diseases in fisherman is dermatitis, lead to clinical abnormalities of polymorphic licensed (erythema, endemias, papules, vesicles, skuama, likenifikasi) and itchy complaints. This study aims to determined the relationship of personal hygiene and the use of personal protective equipment (PPE) with complaints of dermatitis This research used cross sectional research design. The popoluation of studi are all of fisherman in Sugihwaras Village Pemalang district. The number of samples as much as 58 respondents obtained by using accidental sampling method. Data of personal hygiene and the use of PPE were collected by questionnaire. Data of dermatitical complaints were collected by medical person. Data analysis used Chi Square Test. 47% of respondents have poor personal hygiene and 57% of respondents who didn’t weared PPE are at risk of experience complaints of dermatitis in the body. The result of this research can be concluded that there are positive positive relationship between personal hygiene with dermatitis complaint (p value 0,003) PR (95%CI) = 2,01 (1,24 – 3,27), positive positive relationship between the use of personal protective equipment with dermatitis complaint (p value 0,005) PR(95%CI) = 2,02 (1,16 – 3,55). There are relationship between personal hygiene and the use of Personal Protective Equipment (PPE) with complaints of dermatitis.